THE ANTIDEPRESSANT EFFECTS OF PHYSICAL ACTIVITY: NEUROBIOLOGICAL MECHANISMS AND PSYCHOSOCIAL MECHANISMS - Amadeusz Furmanek; Martyna Susek; Mariusz Suchcicki (International Journal of Innovative Technologies in Social Science, 2026)
Background: Depression is a leading cause of disability worldwide, affecting millions and imposing significant personal, social, and economic burdens. While pharmacological and psychotherapeutic interventions are standard treatments, physical activity has emerged as a promising complementary or alternative strategy.Methods: A comprehensive literature review was conducted of peer-reviewed studies published between 2000 and 2025, including randomized controlled trials, meta-analyses, and observational research. Populations examined included adolescents, adults, and older adults. Data extraction focused on depressive symptom outcomes, exercise modalities, intervention duration and intensity, and underlying neurobiological and psychosocial mechanisms.Results: Evidence consistently indicates that regular physical activity, particularly aerobic and combined aerobic–resistance exercise, produces moderate to large reductions in depressive symptoms. Mechanistically, exercise enhances brain-derived neurotrophic factor (BDNF) expression, modulates monoaminergic neurotransmission, regulates the hypothalamic–pituitary-adrenal (HPA) axis, and reduces systemic inflammation. Psychosocial benefits, including behavioral activation, increased self-efficacy, and social engagement, further support sustained mood improvement. Combined interventions often yield the greatest effect, integrating biological, psychological, and social pathways.Conclusion: Physical activity is a safe, accessible, and effective intervention for depression, with benefits extending beyond symptom reduction to improved cognitive function, stress resilience, and overall well-being. Incorporating structured exercise into standard treatment protocols may optimize clinical outcomes and support long-term mental health across diverse populations.